The Current Situation, Hot Spot, and Frontier of the Research on the Employment Pressure of College Students in China (Quantitative Visualization Analysis Based on CNKI Core Literature Library in 2002-2019) - Zhang Yong; Luo Renlian; M. Yoserizal Saragih (Britain International for Academic Research (BIAR) Publisher, 2020)
In order to understand the development of the research on College Students' employment pressure and provide a reference for the research field of College Students' employment pressure, this paper analyzes the current situation, hot spots, and frontier of the research on College Students' employment pressure by using the bibliometric method. The results showed that: the total amount of research on the employment pressure of college students in China showed a significant fluctuation trend; the authors and institutions of the research are distributed in colleges and universities; the research on the employment pressure, social support, mental health education and coping style of college students is the research hotspot and frontier in this field at present.